PENENTUAN KADAR MANGAN (Mn) PADA AIR GAMBUT SECARA SPEKTROFOTOMETRI UV-Vis DENGAN PERBANDINGAN METODE KURVA KALIBRASI DAN ADISI STANDAR (DETERMINATION OF MANGANESE IN PEAT WATER USING UV-Vis SPECTROPHOTOMETER: COMPARATION OF CALIBRATION OF CURVE AND STANDARD ADDITION METHOD) - Emilia Emilia; Lia Destiarti; Adhitiyawarman Adhitiyawarman (Indonesian Journal of Pure and Applied Chemistry, 2021)
Peat water has different characteristics from one location to another. The characteristics referred to include levels of organic matter, pH, conductivity, and turbidity. Based on these differences, it is necessary to research to determine the analytic parameters and the effect of matrix differences on manganese levels using a separate calibration method and standard addition using a Uv-vis spectrophotometer. The determination of manganese was carried out by the persulfate method, that is the oxidation of Mn in water by persulfate in an acidic and hot atmosphere to form MnO4 which is purple-red. The obtained results from the determination of the analytical parameters of the separate calibration method are precision of 7.75% to 63.96%, an accuracy of 0.80% to 5.24%, the linearity of r = 0.997, a detection limit of 0.170 ppm, and a limit of quantification of 0.567 ppm. Meanwhile, the addition method produces a precision of 2.19% to 20.35%, accuracy and linearity at points I, II, III are 10.65% to 25.47% respectively; 20.9% to 26.8%; 2.76% to 27.24% and 0.995; 0.999; 0.995. Linearity in addition as well as in calibration curves at all points have met the minimum value of SNI 6989.5: 2009 (R ≥ 0.995). In addition, based on the results of the comparison of the levels of the separate calibration and standard additions, the values are different, but the results of the t-test result in t-count <t-table. This means that there is no significant difference between separate calibration methods and standard addition.